Single‐fiber F waves compared with conventional surface F waves, and their utility in detecting early diabetic neuropathy. Issue 5 (19th September 2018) - Kamel, Jordan; Knight‐Sadler, ROry; Cook, Mark; Roberts, Leslie
ABSTRACT: Introduction : The single‐fiber F‐wave (SFF‐wave) technique assesses the entire length of single motor fibers using a concentric needle. Herein we investigated the utility of this approach in the detection of early diabetes‐related neuropathy, and compared it with the use of conventional surface F waves (CF waves). Methods : Sixteen patients with diabetes and either no neuropathy or mild neuropathy were assessed and compared with 16 age‐ and height‐matched control participants. Results : Both CF and SFF waves were abnormal in all 5 patients who had mild neuropathy. However, SFF waves demonstrated subclinical abnormalities in 7 of 11 patients (64%) with no neuropathy, whereas only 2 of these patients (18%) had prolonged CF waves. Minimum F‐wave latency was comparable between techniques, but maximum SFF‐wave latency was more frequently prolonged, as these delayed motor units were better isolated, rather than buried among summated CF‐wave responses. Discussion : SFF waves highlight the segmental involvement in diabetic neuropathy, and use of the SFF‐wave technique detects more abnormalities than with CF waves. Muscle Nerve 58 : 665–670, 2018